Respiratory pathogens detected in children aged <5 years hospitalized with severe respiratory illness, South Africa, 2017 - Moleleki, Malefu; Reddy, Cayla; Ndlangisa, Kedibone; du Plessis, Mignon; Hellferscee, Orienka; Mekgoe, Omphe; Walaza, Sibongile; Tempia, Stefano; Cohen, Cheryl; von Gottberg, Anne; Wolter, Nicole (Frontiers in Pediatrics, 2025)
IntroductionThe burden of morbidity and mortality of severe respiratory illness (SRI) remains disproportionately high among young children, and in low-and middle-income countries. We used a multi-pathogen respiratory PCR assay to detect pathogens in children aged <5 years hospitalized with SRI.MethodsProspective syndromic surveillance for SRI was performed at two sentinel hospitals in South Africa between January and December 2017. Nasopharyngeal aspirates and sputa were collected and tested using a real-time polymerase chain reaction based TaqMan Array Card (TAC) for the detection of 21 respiratory pathogens. Pathogen detection was compared by age group using the chi-squared test and seasonal frequency analysed.ResultsFrom January through December 2017, 361 children were enrolled and of these, 198 cases with sufficient specimen volume were included in this study. Overall, 189/198 (95%) of the children tested positive for at least one pathogen. Common viruses identified included rhinovirus (65/198; 33%), respiratory syncytial virus (RSV) (54/198; 27%), adenovirus (34/198; 17%), and enterovirus (28/198; 14%). Common bacteria detected included Haemophilus influenzae (121/198; 61%), Streptococcus pneumoniae (114/198; 58%), Klebsiella pneumoniae (61/198; 31%), Staphylococcus aureus (52/198; 26%), and Acinetobacter baumannii (27/198; 14%).DiscussionBacterial detections were high in our study driven by the high detection of S. pneumoniae and H. influenzae. Co-detections of pathogens were common and require clinical evaluation to determine their relevance in clinical management. Further, given the high prevalence of RSV amongst children hospitalized with SRI, there is an urgent need for continued efforts towards access to maternal RSV vaccines and therapeutic interventions such as monoclonal antibodies particularly in low- and middle-income countries which experience the highest burden of RSV-associated disease.